1982
DOI: 10.1017/s0021859600030148
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of copper status and therapy on fertility in beef suckler herds

Abstract: A survey on 17 beef suckler herds in the north-east of Scotland showed that there was no relationship between herd serum copper concentration (range 0-16-0-92

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…It has been demonstrated that parenteral Cu injection 1 month before the mating season increased plasma Cu levels but did not modify the reproductive performance [18]. In the present study, Cu administration 9 days before ovulation increased the pregnancy rate, suggesting that the beneficial effect of parenteral Cu injection could be related to the time of administration.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…It has been demonstrated that parenteral Cu injection 1 month before the mating season increased plasma Cu levels but did not modify the reproductive performance [18]. In the present study, Cu administration 9 days before ovulation increased the pregnancy rate, suggesting that the beneficial effect of parenteral Cu injection could be related to the time of administration.…”
Section: Discussionsupporting
confidence: 39%
“…In the present study, the plasma Cu concentration of the animals used to evaluate pregnancy rate was below 89 µg/dL Cu (Experiment 4). (b) On the other hand, Cu could have a pharmacological effect on ovarian function and ovulation when applied parenterally, as suggested by Phillippo [18] and Underwood and Suttle [13]. In ruminants, FSH is the principal regulator of follicular growth, whereas LH stimulates large follicles [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There are differing reports in the literature on the effect of low copper (Cu) status on reproduction in cattle. While Cu status was thought to be positively related to reproductive performance in cattle (Bennetts, Beck & Harley, 1948), other reports do not substantiate this (Littlejohn & Lewis, 1960;Seekles & Claessens, 1967;Rowlands, Little & Kitchenham, 1977;Larson, Marbruck & Lowry, 1980;Phillippo et al 1982). Though a positive effect of Cu supplementation on fertility has been claimed under certain circumstances (Blakemore & Venn, 1950;Munro, 1957;Mahadevan & Zubairy, 1969;Sastry et al 1973;Pickering, 1975;Hunter, 1977), no beneficial effect has been reported from controlled trials on an individual farm basis (Poole & Walshe, 1970;Whitaker, 1982;Phillippo et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent work (Phillippo et al 1982) supported the idea that fertility was not related to Cu status and was not improved by Cu treatment, it also indicated that high molybdenum (Mo) intake might be involved in poor reproductive performance. Earlier work had suggested such a relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Altos niveles de molibdeno dietario en rumiantes pueden ocasionar, por sí mismos o a través de su interacción sobre el metabolismo del cobre, diversos trastornos, entre ellos reproductivos, tanto en machos como en hembras 2,3,9,10,13,14 . La molibdenosis es también conocida con el nombre de hipocuprosis secundaria, deficiencia secundaria de cobre o deficiencia condicionada de cobre.…”
Section: Introductionunclassified